PATH SELECTION PRIORITIZATION IN CONTROL FLOW TESTING USING CLUSTERING METHOD - Ikhsan, Muhammad
Software development continues to evolve from time to time until the present day. To ensure the quality of software development, software testing is essential. Software testing techniques are continuously improving both in structural and dynamic aspects. One of the structural testing techniques is control flow testing. However, in practice, there are several issues, such as determining the selection paths criteria to conduct testing on the software or program being tested. The complexity of the software or program will significantly influence the determination of the paths to be executed, where the larger the program under test, the longer and more difficult it is to find execution paths. This research utilizes the prioritization of selection paths criteria using artificial intelligence with clustering techniques in the control flow testing process. Furthermore, the development of an automated tool to search for selection paths criteria is performed to make the path search process faster and more efficient. The results of the research conducted on several modules and software showed coverage values with the highest average of 44%, 66%, 68%, and 100%, with the required time ranging from 0 to approximately 53 seconds..